2014
DOI: 10.1155/2014/435857
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Omega-3 Polyunsaturated Fatty Acid against Lead Acetate-Induced Toxicity in Liver and Kidney of Female Rats

Abstract: The present study was conducted to investigate the protective role of Omega-3 polyunsaturated fatty acids against lead acetate-induced toxicity in liver and kidney of female rats. Animals were divided into four equal groups; group 1 served as control while groups 2 and 3 were treated orally with Omega-3 fatty acids at doses of 125 and 260 mg/kg body weight, respectively, for 10 days. These groups were also injected with lead acetate (25 mg/kg body weight) during the last 5 days. Group 4 was treated only with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 43 publications
23
75
0
1
Order By: Relevance
“…In the study done by Takase et al in 2011 it was indicated that EPA blocked the development of tubulointersititial damage in models with Thy-1 nephritis and had inhibitory effects on inflammatory molecules by regulating IKBa in cultured renal cells [24]. The study that Abdou et al conductd in 2014 declared that omega-3 fatty acids prevented renal toxicity induced by lead in rats [25]. Peake et al in 2011 concluded that consuming fish oils prevented the oxidative stress, fibrosis and inflammation related to kidney damage in rats [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the study done by Takase et al in 2011 it was indicated that EPA blocked the development of tubulointersititial damage in models with Thy-1 nephritis and had inhibitory effects on inflammatory molecules by regulating IKBa in cultured renal cells [24]. The study that Abdou et al conductd in 2014 declared that omega-3 fatty acids prevented renal toxicity induced by lead in rats [25]. Peake et al in 2011 concluded that consuming fish oils prevented the oxidative stress, fibrosis and inflammation related to kidney damage in rats [26].…”
Section: Discussionmentioning
confidence: 99%
“…All groups were subjected to a 10-day experiment as follows: Group 1 (negative control): 0.5ml saline (0.9%NaCl), intraperitoneally (IP) for 10 days. Group 2: 25 mg/kg lead acetate (Merck, Germany), IP for the last 5 days [14]. …”
Section: Experimental Designmentioning
confidence: 99%
“…The Target hazard quotient (THQ) for the metals in the current study showed that Cr > Pb > Cd > Cu > Ni with all the values < 1 suggesting minimal risk of non carcinogenic consequence but Cr showed higher potential health risk than other metals. THQ > 1 has been said to indicate potentials of non carcinogenic risk to human exposures [42,43,44] particularly with increase in metal exposure. The THQ of metals in this study (<1) agrees with the findings of [45] and [46] but disagreed with the findings of [47] who reported >1 THQ for Pb, Cr, and Hg in fish from the coast of India.…”
Section: Discussionmentioning
confidence: 99%